Microbial synthesis of violacein pigment and its potential applications - Park, Hyun A.; Park, Seo A.; Yang, Yung Hun; Choi, Kwon Young (Critical Reviews in Biotechnology, 2021)
Violacein is a pigment synthesized by Gram-negative bacteria such as Chromobacterium violaceum. It has garnered significant interest owing to its unique physiological and biological activities along with its synergistic effects with various antibiotics. In addition to C. violaceum, several microorganisms, including: Duganella sp., Pseudoalteromonas sp., Iodobacter sp., and Massilia sp., are known to produce violacein. Along with the identification of violacein-producing strains, the genetic regulation, quorum sensing mechanism, and sequence of the vio-operon involved in the biosynthesis of violacein have been elucidated. From an engineering perspective, the heterologous production of violacein using the genetically engineered Escherichia coli or Citrobacter freundii host has also been attempted. Genetic engineering of host cells involves the heterologous expression of genes involved in the vio operon and the optimization of metabolic pathways and gene regulation. Further, the crystallography of VioD and VioE was revealed, and mass production by enzyme engineering has been accelerated. In this review, we highlight the biologically assisted end-use applications of violacein (such as functional fabric development, nanoparticles, functional polymer composites, and sunscreen ingredients) and violacein activation mechanisms, production strains, and the results of mass production with engineered methods. The prospects for violacein research and engineering applications have also been discussed.
Keywords: Activation mechanisms; Chromobacterium violaceum; Engineered escherichia coli; Engineering applications; Engineering perspective; Gram-negative bacteria; Heterologous expression; Heterologous production; Chromobacterium; Indoles; Quorum Sensing; biological activity; Chromobacter violaceum; heterologous production; indole derivative; L-tryptophan; VioABCDE; Violacein